Impact of political conflict on tuberculosis notifications in North-east Nigeria, Adamawa State: a 7-year retrospective analysis. Issue 9 (16th September 2020) - Pembi, Emmanuel; John, Stephen; Dumre, Shyam Prakash; Ahmadu, Baba Usman; Vuong, Nguyen Lam; Ebied, Amr; Mizukami, Shusaku; Huy, Nguyen Tien; Cuevas, Luis E; Hirayama, Kenji
Abstract : Objective: We assessed the impact of political conflict (Boko Haram) on tuberculosis (TB) case notiﬁcations in Adamawa State in North-east Nigeria. Design: A retrospective analysis of TB case notifications from TB registers (2010–2016) to describe changes in TB notification, sex and age ratios by the degree of conflict by local government area. Setting: Adamawa State. Participants: 21 076 TB cases notified. Results: 21 076 cases (62% male) were notiﬁed between 2010 and 2016, of which 19 604 (93%) were new TB cases. Areas affected by conflict in 2014 and 2015 had decreased case notification while neighbouring areas reported increased case notifications. The male to female ratio of TB cases changed in areas in conflict with more female cases being notified. The young and elderly (1–14 and >65 years old) had low notifications in all areas, with a small increase in case notifications during the years of conflict. Conclusion: TB case notifications decreased in conflict areas and increased in areas without conflict. More males were notified during peace times and more female cases were reported from areas in conflict. Young and elderly populations had decreased case notifications but experienced a slight increase during the conflict years. These changes are likely to reflect population displacement and a dissimilar effect of conflict on the accessibility of services. TB services in conflict areas deserve further study to identify resilient approaches that could reach affected populations.